Youth and political violence: Straker, G with Moosa, M, Becker, R, & Nkwale, M (1992) Faces in the revolution: The psychological effects of violence on township youth in South Africa. Cape Town: David Philip, ISBN 0-86486-203-2. Ohio: Ohio University Press, ISBN 0-8214-1040-7. - Gibson, Kerry (PINS-Psychology in Society, 2026)
Much of the psychological literature on political violence has tended to tell us more about the ways in which psychiatrists and psychologists categorise, code and evaluate the responses of the victims than about the people who are actively living through, making sense of and fighting against these things. Straker et al's Faces in the Revolution has managed the much more difficult task of transmitting something of the psychological complexity of the lived experience of youth during the repression of the 1980s.